TEXTUAL FUNCTION ANALYSIS OF CRIMINAL TEXT IN DER SPIEGEL ONLINE 2022 - Sahat Taruli Siahaan; Vita Riahni Saragih; Lusiana Simamora (Jurnal Scientia, 2022)
This study aims to analyze the textual function of the criminal text in the online magazine Der Spiegel Online 2022. The data of this research are German sentences that collect 101 sentences from 6 criminal articles. The data sources for this research are 6 crime articles from the online magazine Der Spiegel Online published in August 2022. The six criminal text titles in sequence are: 1) Tödliche Schüsse in Malmö Mutmaßlicher Täter ist 15 Jahre alt; 2) Polizeieinsatz in Malmö Ein Toter und eine Verletzte nach Schüssen in Einkaufszentrum; 3) Misteriöser Criminalfall in Ingolstadt Vermeintliches Gewaltopfer lebend gefunden – und festgenommen; 4) Ermittlungen at zwei Ländern 32-jähriger Mainzer in Mexico durch Schüsse verletzt; 5) Mindestens 20 Kilogramm wertvoller Abfall Mann schmuggelt Goldspäne aus Trauringfabrik – fast vier Jahre Haft; and 6) Freiheitsstrafe für 93-Jährige Urteil gegen Ursula Haverbeck ist rechtskräftig. The theory used in this study is Halliday's Systemic Functional Linguistics. The technical model approach of the data analysis of this research is from Eggins (2004) regarding patterns of thematic choice: marked theme and unmarked theme. Based on the results of research data analysis, the results of this study are: 1) types of thematic choice patterns in criminal texts in Der Spiegel Online 2022 in August there are 2 types, that is 60 items (59%) unmarked themes and the marked theme as much as 41 items (41%); 2) The dominance of the thematic choice pattern in criminal texts in Der Spiegel Online 2022 in August, that is the unmarked theme.